Vulnerabilidade da pessoa idosa: desenvolvimento do conceito - Barbosa, Keylla Talitha Fernandes (2019)
Introduction: Vulnerability is a multidimensional construct in which behavioral, socio-cultural, economic and political conditions interact with life-long biological processes. Little studied in gerontology, the concept of vulnerability in the elderly person needs to be built from the specificities arising from the natural process of human aging, contributing to the expansion of comprehensive care to the elderly person. Objective: To develop the concept of vulnerability of the elderly person based on the Hybrid Concept Development Model. Method: This is a descriptive methodological study with a qualitative approach, based on the theoretical-methodological framework of the Hybrid Concept Development Model, consisting of three phases: theoretical, empirical and final analytical. For the development of the theoretical phase, an integrative literature review was carried out from publications on the Theses and Dissertations Database of the Higher Education Personnel Improvement Coordination, Cumulative Index to Nursing and Allied Health Literature, Latin American and Latin American Literature. Caribbean in Health Sciences, Medical Literature Analysis and Retrieval Online systems, SciVerse Scopus and Web of Science, using the following descriptors: health vulnerability, aged, health services for the elderly person and health of the elderly person. Then, the empirical phase was developed through a semi-structured interview with 12 professionals (including nurses, psychologists, nutritionists, physiotherapists and social workers) with work or academic experience in the care of the elderly. The Grounded Theory was used as a method of analysis of the interviews. The final analytical phase constituted the interface between theoretical and empirical evidence. This study was reviewed by the Ethics Committee of the Health Sciences Center of the Federal University of Paraíba and approved under Opinion n. 1,984,562. Results: When conducting the theoretical survey, 36 studies were listed to compose the integrative literature review, which supported the delineation of the attributes, antecedents and consequences of the studied phenomenon. Moreover, the theoretical evidence allowed the definition of the concept to be worked in the subsequent phase. The data analysis, through the Grounded Theory, originated two phenomena: 1 - Unveiling the multiple changes resulting from the human aging process and 2 - Understanding the multiple dimensions of the vulnerability construct of the elderly person, which allowed the approach to the theme from the perspective of health professionals. Finally, anchored in the speeches of the study participants and the relevant literature, the concept of vulnerability of the elderly person was elaborated. Final thoughts: The vulnerability of the elderly person is a multifaceted construct, in which individual and collective conditions interact with each other, determining the reduction of the ability to cope with health problems. Given the aging of the population, it is essential to recognize the heterogeneity of senescence and thus stimulate the development of practices compatible with the values, social, financial and structural conditions of the population in question.